Construction problems of volume protected by airtermination rod for the ukrainian nuclear power plant under standard EN 62305 - Istomin, О.Ye.; Koliushko, D.G.; Kiprych, S.V.; Rudenko, S.S. (Вопросы атомной науки и техники, 2019)
Mathematical analysis of the rolling sphere method was performed to develop a model for constructing of volume protected by rod air-termination in accordance with EN 62305:2012 for the protection of nuclear power plants objects from direct lightning strike. The necessity of development of the corresponding mathematical model for similar objects is shown, and the direction of its realization with the help of decomposition method is proposed. The mathematical models for calculation of protection zones of single and double air-termination rods of arbitrary height and location are developed. Directions of further researches are formed. Виконано математичний аналіз методу сфери, що котиться, для розробки моделі побудови зон захисту складної системи блискавковідводів згідно з ДСТУ EN 62305:2012 для захисту об’єктів атомних електричних станцій від прямого удару блискавки. Показана необхідність розробки відповідної математичної моделі для подібних об’єктів та запропоновано напрямок її реалізації за допомогою методу декомпозиції. Розроблено математичні моделі для розрахунку зон захисту одиничного та подвійного стрижньових блискавковідводів довільної висоти і розташування. Сформовано напрями подальших досліджень. Выполнен математический анализ метода катящейся сферы, для разработки модели построения зон защиты сложной системы молниеотводов согласно ДСТУ EN 62305: 2012 для защиты объектов атомных электрических станций от прямого удара молнии. Показана необходимость разработки соответствующей математической модели для подобных объектов и предложены направление реализации с помощью метода декомпозиции. Разработаны математические модели для расчета зон защиты одиночного и двойного стержневых молниеотводов произвольной высоты и расположения. Сформированы направления для дальнейших исследований.